Failure iridocapsular fixation of IOL in patients with lens subluxation (preliminary report) - I. E. Ioshin; A. I. Tolchinskaya; S. A. Dubrovskaya (Российский офтальмологический журнал, 2019)
Purpose. To present the preliminary results of iridocapsular fixation of RSP-3 extracapsular IOL in patients with lens subluxation observed within the first year after surgery.Material and methods. 4 patients with cataracts and initial weakness of Zinn ligament fibers were followed up. YAG laser iridectomy was performed one day before facoemulsifcation surgery, which took account of Zinn ligament fiber weakness: it consisted in anterior continuous circular capsulorhexis with a diameter of about 5 mm, fixation of the capsular bag over the edge of capsulorhexis with four iris-capsular retractors (ICRs), phacoemulsification of the nucleus and aspiration of lens masses. The intracapsular ring and the RSP-3 IOL (the latter in the injector through the main incision) was implanted in such a way as to locate the rear support element in the capsular bag, and the front support element, in front of the pupil. After removing the ICRs, iridectomy was monitored.Results. The early postoperative period was uncomplicated. After 10 days, one patient was found to develop a relative pupillary block with the anterior chamber becoming shallower and IOP increased to reach 28 mm Hg. The reason was that iridectomy initially located in the projection area of the rear support element. An additional iridectomy arrested the situation. Visual acuity varied from 0.3 to 1.0 due to the initial state of the optic nerve and retina. The position of the IOL remained stable throughout the year, the capsular bag was unfolded.Conclusion. The possibility to use the capsular bag of the lens under the conditions that Zinn ligament fibers are weak should be considered as an advantage of the technology presented. An additional front support element serves to prevent dislocation of the IOL and the capsular bag as a whole. The obtained positive results of combined iridocapsular fixation of the IOL justify a more extensive clinical testing of the method in cases of weak Zinn ligament fibers.